DINAMIKA TAKSONOMI BLOOM DAN RELEVANSI DENGAN PENDIDIKAN ISLAM - Jamaluddin, Ahmad; Hikam Darman, Muhammad; Tacong, Kamaluddin; Damopolii, Muljono; Saprin (Primer Edukasi Journal, 2026)
While many studies on Bloom's Taxonomy have been conducted in the context of general education, few have specifically examined its relevance in depth to Islamic Education. This gap creates a need to explore how the cognitive framework of Bloom's Taxonomy can be adapted and applied to achieve the goals of a holistic Islamic Education, emphasizing not only intellectual aspects but also spiritual and moral aspects. The purpose of this study is to analyze the dynamics of the evolution of Bloom's Taxonomy and identify points of contact and potential integration with the philosophy and practice of Islamic Education. Using a comprehensive library research method, this study will examine various literature on Bloom's Taxonomy, Islamic educational theories, and articles discussing curriculum and teaching methods in the Islamic context. This approach is expected to produce a richer understanding of how Bloom's Taxonomy can be an effective tool in designing relevant and meaningful learning in Islamic Education, supporting the development of students with critical and creative thinking skills grounded in Islamic values.